Applying PhET Interactive Simulations Media With A Guided Investigation Approach to Improve Student’s Critical Thinking Skills - Yunitasari, Yunitasari; Firdaus, M. Lutfi; Wardana, Rendy Wikrama; Putra, Syalendra (Universitas PGRI Semarang, 2024)
The purpose of this research is implementation PhET Interactive Simulations Media with a Guided Inquiry Approach to Improve Students' Critical Thinking Skills